Comparative Evaluation of Seed Treatment Methods for Optimum Germination and Growth of Moringa Oleiferain Pothohar Region (Journal of Asian Development Studies, 2026)
Moringa oleifera is a fast-growing, multipurpose tree species. It is high in protein and is used for human consumption, animal feed, and medicine. The aim of this study was to determine the adaptability of four landraces of Moringa oleifera at Koont Research Farm of Pir Mehr Ali Shah, Arid Agriculture University, Rawalpindi. Seeds were sown in polythene bags in the nursery after control, hot-water, and tap-water seed treatments. The germination and growth potential were assessed by using different parameters. Seed germination was recorded for three weeks in the laboratory and in nursery conditions, and the data were statistically analysed using ANOVA. Controlled water-seeding treatment enhances the germination potential of different landraces. Hot water treatment shows significant value in growth parameters. It is recommended that Moringa oleifera be treated with water to enhance the germination and growth parameters in the Pothwar region. So, it can be grown in other countries.